ANALISIS PEMASARAN INDUSTRI KECIL PADA EVEN WISATA PACU JALUR KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Laila Ramadhana; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this research aims to determine the perception of tourist to the small industry’s people on track racing event in Kuantan Singingi Regency.This research use descriptive methode to analyze the problems. The sampel inside this research are 50 respondence by usung accidental sampling. And then tecnique to collected data in this research are using observation, questionnaire, and interview. And it was using likert scale to know the lenght of intervals.Based on the researh of the small marketing people,less productive because of lack attention to create a new bussines, foe example there is not a strore or a special place that provides souvenir, less attractive packaging, bad quality of the product altought the capital to make the souvenirs are not good. And the most of tourist who visit come from premises.Key words : Marketing, Tourism industry, Track racing even, Tourism